(3MOjbI GdRgQ aj YOO Bi GdShQs - (3HQgGf GdOjf EHQGgje Hf CHj HcQ GdLYHQj,J (B687 (3g` s
(3ChdgG (B:s
(3HOCJ HMeO Gddg Chd ebUOi hUdJ HYOg Ydi GdWgQ CMeO s
(3hgj bUjOI OGdjI (B58 (3HjJkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B8 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs